Metodologi Argumentasi Hukum dalam Tafsir al-Jami' li Ahkam al-Qur'an al-Qurtubi: Methodology of Legal Argumentation in Tafsir al-Jami li Ahkam al-Qur'an by al-Qurtubi - Najwa Rihan Zahara (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2026)
This study examines the methodology of legal argumentation (al-manahij al-istidlaliyah) employed by al-Qurtubi in his Tafsir al-Jami li Ahkam al-Quran. Previous studies on al-Qurtubis tafsir have generally focused on the thematic discussion of legal verses, the legal rulings he derived, or the overall characteristics of his legal exegesis; however, these works remain largely descriptive and have not specifically analyzed the epistemological structure and argumentative framework underlying his process of deriving legal rulings. This gap has led to a limited understanding of al-Qurtubis tafsir, which is often viewed solely through its legal conclusions, without examining the methodological reasoning that connects textual evidence to those conclusions. This study addresses that gap by reconstructing al-Qurtubis pattern of legal argumentation through an analysis of his use of scriptural evidence, linguistic reasoning, principles of usul al-fiqh, considerations of maqasid al-shariah, and his systematic mechanism of tarjih. Using a qualitative library research approach, the study finds that al-Qurtubi integrates Quranic and prophetic texts with rational legal reasoning and juristic principles to construct a coherent, structured model of legal interpretation. The novelty of this research lies in its systematic reconstruction of al-Qurtubis methodological framework, demonstrating how tafsir methodology and juristic reasoning converge to form a rigorous and contextually relevant model of Islamic legal argumentation.